Anatomical Variation of Left Internal Mammary Artery and Thyrocervical Trunk: A Case Report - Ji-Yeon Han; Jinwook Baek (Neurointervention)
We report a rare case of a left internal mammary artery (LIMA) originating from the left thyrocervical trunk (TCT), which arose directly from the aortic arch. A patient in their 70s presented with bilateral distal internal carotid artery aneurysms, diagnosed through computed tomography angiography performed for headache evaluation. Transfemoral cerebral angiography confirmed the aneurysms and incidentally revealed the anomalous origins of the TCT and LIMA, as well as a left vertebral artery directly arising from the aortic arch. This case emphasizes the importance of recognizing such rare anatomical variations prior to diagnostic or interventional procedures. Thorough preoperative evaluation is critical to avoid complications, particularly in coronary artery bypass grafting and head and neck tumor embolization.